Evaluation of the association of prostate cancer‐specific anxiety with sexual function, depression and cancer aggressiveness in men 1 year following surgical treatment for localized prostate cancer. Issue 6 (1st August 2012) - Tavlarides, Andrea M.; Ames, Steven C.; Diehl, Nancy N.; Joseph, Richard W.; Castle, Erik P.; Thiel, David D.; Broderick, Gregory A.; Parker, Alexander S.
Abstract Background Cancer‐specific anxiety (CSA) can affect treatment decisions and is common in men following surgery for prostate cancer (PCa). We hypothesized that CSA is also associated with factors affecting quality of life. Herein, we examine the association of CSA with psychosocial factors and PCa aggressiveness in a cohort of men 1 year after prostatectomy for localized PCa. Methods From our prospective PCa Registry, we identified 365 men who underwent prostatectomy for localized PCa who completed the Memorial Anxiety Scale for Prostate Cancer (MAX‐PC) and Expanded Prostate Cancer Index Composite at 1‐year follow‐up. We evaluated the association of scores on the MAX‐PC with demographics, clinicopathologic features, sexual function, and depression scores using Wilcoxon Rank Sum and Kendall's tau correlation tests. Results Higher scores on the MAX‐PC (i.e., higher anxiety) are associated with younger age (p < 0.01) and non‐Caucasian race (p < 0.01). Men with higher MAX‐PC scores also reported poor sexual satisfaction/function (p < 0.01) and increasing depressive symptoms (p < 0.01). Finally, although higher anxiety is associated with several pathologic features of aggressiveness (stage, positive margins, PSA at 1 year; all p‐values < 0.01), we noted several men with clinically indolent disease who reported significant anxiety. Conclusions Our data suggest that higher levels of CSA are associated with poor sexual function and increased depressive symptoms 1 year after prostatectomy. Moreover, we noted demographic and pathologic features associated with higher CSA as well. If confirmed, our data support development of models to predict men at high risk of CSA following PCa surgery and targeted referral for additional counseling. Copyright © 2012 John Wiley & Sons, Ltd.